Autophagy activation contributes to glutathione transferase Mu 1-mediated chemoresistance in hepatocellular carcinoma - Fu, Xiu-Tao (Oncol Lett, 2018)
Glutathione transferase Mu 1 (GSTM1) induces cancer drug resistance by hydrolyzing cancer chemotherapeutics or activating the anti-apoptosis pathway. However, the chemoresistance-inducing mechanism of GSTM1 in hepatocellular carcinoma (HCC) remains unknown. In the present study, the expression of GSTM1 was examined in three HCC cell lines. Oxaliplatin and sorafenib were selected as chemotherapeutic agents. Small interfering RNA was used to decrease GSTM1 expression. Cell death was measured using MTT and annexin V/propidium iodide assays. Activation of autophagy was evaluated by green fluorescent protein-light chain 3 redistribution and analysis of autophagy-related 5 expression in MHCC97-H and Huh-7 cells. A stepwise increase in GSTM1 expression with increasing metastatic potential of HCC cell lines was revealed. Cell death induced by oxaliplatin and sorafenib was significantly increased following GSTM1-knockdown in MHCC97-H and Huh-7 cells. Activation of autophagy was significantly inhibited by silencing GSTM1 expression. The results of the present study suggest that GSTM1 may protect HCC cells against the effect of oxaliplatin treatment through activating autophagy. The present study provides a novel perspective on HCC drug-resistance.